2020
DOI: 10.1001/jamanetworkopen.2019.21636
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Dual Decline in Memory and Gait Speed With Risk for Dementia Among Adults Older Than 60 Years

Abstract: IMPORTANCE Dual decline in both memory and gait speed may characterize a group of older individuals at high risk for future dementia. OBJECTIVE To assess the risk of dementia in older persons who experience parallel declines in memory and gait speed compared with those who experience no decline or decline in either memory or gait speed only. DESIGN, SETTING, AND PARTICIPANTS A multicohort meta-analysis was performed of 6 prospective cohort studies conducted between 1997 and 2018 in the United States and Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 58 publications
2
48
0
Order By: Relevance
“…In the typically developing population, decreases in gait velocity 33–35 occur in aging. For gait velocity, these changes are most evident after age 60, 33 with an exponential decline in gait speed after age 80 34 . Given the current cohort had a maximum age of 59 and average age of 37, it is promising that dual‐task gait velocity tended to be slower as it may then indicate early effects of brain pathologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the typically developing population, decreases in gait velocity 33–35 occur in aging. For gait velocity, these changes are most evident after age 60, 33 with an exponential decline in gait speed after age 80 34 . Given the current cohort had a maximum age of 59 and average age of 37, it is promising that dual‐task gait velocity tended to be slower as it may then indicate early effects of brain pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…We found that gait speed was tended to be slower in older individuals during dual‐task conditions, but remained relatively stable during the self‐paced condition. In the typically developing population, decreases in gait velocity 33–35 occur in aging. For gait velocity, these changes are most evident after age 60, 33 with an exponential decline in gait speed after age 80 34 .…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies suggest that motoric cognitive risk syndrome or cognitive frailty is associated with high risks of cognitive impairment, dementia, and other adverse health outcomes [34,63]. However, cognitive frailty assessment is typically operationalized at one time point.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, individuals who exhibit both cognitive and motor deficits may have greater underlying brain damage [71]. This implies that the simultaneous analysis of cognitive and physical function may help identify a subset of MCI persons at greater risk of conversion to dementia [71,74]. The observation that low muscle mass is commonly observed in conjunction with cognitive impairment [75,76] suggests that the inclusion of body composition analysis might further refine the identification of people more likely to progress from MCI to dementia.…”
Section: Discussionmentioning
confidence: 99%